Sosialisasi Mitigasi Bencana Alam bagi Masyarakat di Distrik Mamyambouw, Kabupaten Pegunungan Arfak : Pengabdian Masyarakat - Yammes Jonas Batkunde; Irmawati Leppang (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mamyambouw District is in the Arfak Mountains Regency, with a very steep slope, in May 2024 there was a landslide disaster which resulted in loss of property and life. The method for implementing community service in the Mamyambouw District consists of 3 (three) stages, namely: (1) Preparation stage; At this preparation stage, the service team explores information related to communities that have a direct impact on natural disasters and the lowest levels of government at the RT/RW level; sub-district and district levels, then with the Disaster Management Agency. After getting the information, the next step is to determine and prepare socialization materials; 2) Implementation; After preparing the material, the next stage is conducting socialization and questions and answers. In the socialization method, it is hoped that the community will participate actively so that mitigation can be identified early and mitigation related to natural disasters experienced; 3) Closing. The large number of natural disasters that occur does not make the government in general and society in particular lose their minds in managing disasters. At a minimum, the public must have knowledge about disasters obtained independently through media reporting, even though this is actually the Government's responsibility to provide information and education.